Epistemology and Methodology of Islamic Studies in Contemporary Research: A Systematic Literature Review - Zamzami Syandana; Zainab, Nurul; Wahyuni, Amalia Desy; Alatas, Moh. Muhsin (Kartika: Jurnal Studi Keislaman, 2026)
The conceptualization of Islamic Studies as a discipline that is developing progressively within academic discourse and socio-religious practice. Islamic studies are essentially not only oriented toward normative-theological understanding, but also require engagement with historical, philosophical, and socio-humanities approaches to provide a comprehensive picture of the dynamics of Islamic scholarship. This study uses the Systematic Literature Review (SLR) method to comprehensively examine the epistemology and methodology of Islamic studies in contemporary academic discourse. Furthermore, developments in globalization, modernization, and socio-political change have influenced the direction and methods of Islamic studies, thus demanding flexibility and openness in developing conceptual frameworks. The research findings emphasize that Islamic studies cannot be understood in a singular sense, but rather as an open, critical, and transformative intellectual field. The conceptualization offered in this article emphasizes the importance of strengthening the epistemological, methodological, and social relevance aspects of Islamic studies, so that it remains adaptive and contributing to addressing the challenges of the times. Thus, Islamic studies can continue to develop as a discipline that not only maintains religious authenticity but is also relevant in the context of modern science and the needs of global society